Juvenile ocular myasthenia gravis in association with thymolipoma - Kavita Mardi; Neha Bakshi (Sahel Medical Journal, 2013)
Thymolipomas are uncommon tumors of anterior mediastinum. Their association with juvenile ocular myasthenia gravis is extremely rare. A 14-year-old boy presented with ptosis of 2 years and left-sided diplopia of 19 months duration. On examination external ophthalmoplegia and ptosis were present. Generalized muscle weakness was absent. On a neostigmine challenge test, the boy showed improvement in symptoms after 20 minutes of neostigmine injection. Anticholinesterase antibodies and antinuclear antibodies were negative. Chest CT revealed a soft tissue mass in the anterior mediastinum. Histopathological examination of the excised mass was diagnostic of thymolipoma.